Standardization of the school aptitudes Test TAE, Levels 1 and 2 - Ruiz Alva, César (2002)
The present is the result of the standardization of the Test School Aptitudes T AE levels 1 and 2, for which I apply 5980 students of the 3ro. to 6 to. of primary and of lro. To 5to. of secondary whose ages fluctuated among the 8 to 16 years, of the total one muestral, 2580 they corresponds to the primary and 3400 at the secondary level. The dependability of the test by the method of the halves for the TAE 1 I throw coefficients of 0,90 ace minimum to 0,93 at most and for the TAE 2 of 0,89 ace minimum to 0,92. The validity was performed by means of the concurrent method correlating the results with the academic performance in the subjects of mathematics, language and performance in general, likewise, I am correlated with the test factor g forms 2 adapted by the grants a doctorate Nelly Ugarriza. The norms elaborated for chronology age in the intellectual scale coefficient and also by school degrees.